Square of a Trinomial
How to expand the square of a trinomial?
The square of the sum of three or more
terms can be determined by the formula of the determination of the square of
sum of two terms.
Now we will learn to expand the square of
a trinomial (a + b + c).
Let (b + c) = x
Then (a + b + c)
^{2} = (a + x)
^{2} = a
^{2} + 2ax + x
^{2}
= a
^{2} + 2a (b + c) + (b + c)
^{2}
= a
^{2} + 2ab + 2ac + (b
^{2} + c
^{2} + 2bc)
= a
^{2} + b
^{2} + c
^{2} + 2ab + 2bc + 2ca
Therefore, (a + b + c)
^{2} = a
^{2} + b
^{2} + c
^{2} + 2ab + 2bc + 2ca
● (a + b - c)
^{2} = [a + b + (-c)]
^{2}
= a
^{2} + b
^{2} + (-c)
^{2} + 2ab + 2 (b) (-c) + 2 (-c) (a)
= a
^{2} + b
^{2} + c
^{2} + 2ab – 2bc - 2ca
Therefore, (a + b - c)
^{2} = a
^{2} + b
^{2} + c
^{2} + 2ab – 2bc - 2ca
● (a - b + c)
^{2} = [a + (- b) + c]
^{2}
= a
^{2} + (-b
^{2}) + c
^{2} + 2 (a) (-b) + 2 (-b) (-c) + 2 (c) (a)
= a
^{2} + b
^{2} + c
^{2} – 2ab – 2bc + 2ca
Therefore, (a - b + c)
^{2} = a
^{2} + b
^{2} + c
^{2} – 2ab – 2bc + 2ca
● (a - b - c)
^{2} = [a + (-b) + (-c)]
^{2}
= a
^{2} + (-b
^{2}) + (-c
^{2}) + 2 (a) (-b) + 2 (-b) (-c) + 2 (-c) (a)
= a
^{2} + b
^{2} + c
^{2} – 2ab + 2bc – 2ca
Therefore, (a - b - c)
^{2} = a
^{2} + b
^{2} + c
^{2} – 2ab + 2bc – 2ca
Worked-out examples on square of a trinomial:
1. Expand each of the following.
(i) (2x + 3y + 5z)
^{2}
Solution:
(2x + 3y + 5z)
^{2}
We know, (a + b + c)
^{2} = = a
^{2} + b
^{2} + c
^{2} + 2ab + 2bc + 2ca
Here a = 2x, b = 3y and c = 5z
= (2x)
^{2} + (3y)
^{2} + (5z)
^{2} + 2 (2x) (3y) + 2 (3y) (5z) + 2 (5z) (2x)
= 4x
^{2} + 9y
^{2} + 25z
^{2} + 12xy + 30yz + 20zx
Therefore, (2x + 3y + 5z)
^{2} = 4x
^{2} + 9y
^{2} + 25z
^{2} + 12xy + 30yz + 20zx
(ii) (2l – 3m + 4n)
^{2}
Solution:
(2l – 3m + 4n)
^{2}
We know, (a - b + c)
^{2} = a
^{2} + b
^{2} + c
^{2} – 2ab - 2bc + 2ca
Here a = 2l, b = -3m and c = 4n
(2l + (-3m) + 4n)
^{2}
= (2l)
^{2} + (3m)
^{2} + (4n)
^{2} + 2 (2l) (-3m) + 2 (-3m) (4n) + 2 (4n) (2l)
= 4l
^{2} + 9m
^{2} + 16n
^{2} – 12lm – 24mn + 16nl
Therefore, (2l – 3m + 4n)
^{2} = 4l
^{2} + 9m
^{2} + 16n
^{2} – 12lm – 24mn + 16nl
(iii) (3x – 2y – z)
^{2}
Solution:
(3x – 2y – z)
^{2}
We know, (a - b - c)
^{2} = a
^{2} + b
^{2} + c
^{2} – 2ab + 2bc – 2ca
Here a = 3x, b = -2y and c = -z
[3x + (-2y) + (-z)]
^{2}
= (3x)
^{2} + (-2y)
^{2} + (-z)
^{2} + 2 (3x) (-2y) + 2 (-2y) (-z) + 2 (-z) (3x)
= 9x
^{2} + 4y
^{2} + z
^{2} – 12xy + 4yz – 6zx
2. Simplify a + b + c = 25 and ab + bc + ca = 59.
Find the value of a
^{2} + b
^{2} + c
^{2}.
Solution:
According to the question, a + b + c = 25
Squaring both the sides, we get
(a+ b + c)
^{2} = (25)
^{2}
a
^{2} + b
^{2} + c
^{2} + 2ab + 2bc + 2ca = 625
a
^{2} + b
^{2} + c
^{2} + 2(ab + bc + ca) = 625
a
^{2} + b
^{2} + c
^{2} + 2 × 59 = 625 [Given, ab + bc + ca = 59]
a
^{2} + b
^{2} + c
^{2} + 118 = 625
a
^{2} + b
^{2} + c
^{2} + 118 – 118 = 625 – 118 [subtracting 118 from both the sides]
Therefore, a
^{2} + b
^{2} + c
^{2} = 507
Thus, the formula of square of a trinomial
will help us to expand.
7th Grade Math Problems
8th Grade Math Practice
From Square of a Trinomial to HOME PAGE
Didn't find what you were looking for? Or want to know more information
about Math Only Math.
Use this Google Search to find what you need.
Share this page:
What’s this?
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.